Does Servant Leadership Overcome Teacher Burnout? Principal's Strategic Approach - Zukhairina, Zukhairina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study analyses servant leadership in overcoming teacher burnout at an early childhood education institution in Jambi Province. This study uses a qualitative approach, in which observation, interviews and documentation are used as a medium for collecting data. The data analysis was carried out circularly, starting from data collection, reduction, presentation, and conclusion. The study results show several efforts made by the principal to overcome teacher boredom, including; establishing communication forums, stewardship, and community building. This research has implications for the importance of fostering teacher self-confidence and the ability of school principals to establish emotional closeness between school members to move school members to be actively involved in realizing common goals.